2021
DOI: 10.3847/1538-3881/abf6ca
|View full text |Cite
|
Sign up to set email alerts
|

The Rarity of Very Red Trans-Neptunian Objects in the Scattered Disk

Abstract: We investigate the origins of the photometrically very red (VR) and less red (LR) trans-Neptunian objects (TNOs). We first reanalyze the data set of Marsset et al. and find that in addition to the known color–inclination correlation in hot TNOs, a similar trend exists for color–eccentricity. We show that VR TNOs are sharply constrained to eccentricities <0.42 and inclinations <21°, leading to a paucity of VR scattered disk and distant mean motion resonance objects. We then interpret these findings using … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…They only investigated an inner neutral/outer red primordial disk due to the predominantly neutral-colored surfaces of Neptune's Trojans and proposed a color transition position between 30 and 40 au. Similarly, Ali-Dib et al (2021) used N-body simulations to find an inner neutral/outer red disk with a color transition between ∼38 and 42 au based on the lack of red surface KBOs at higher eccentricities. Both of these works found that the inner neutral/outer red disk is consistent with the modern-day Kuiper Belt colors, in agreement with our findings.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…They only investigated an inner neutral/outer red primordial disk due to the predominantly neutral-colored surfaces of Neptune's Trojans and proposed a color transition position between 30 and 40 au. Similarly, Ali-Dib et al (2021) used N-body simulations to find an inner neutral/outer red disk with a color transition between ∼38 and 42 au based on the lack of red surface KBOs at higher eccentricities. Both of these works found that the inner neutral/outer red disk is consistent with the modern-day Kuiper Belt colors, in agreement with our findings.…”
Section: Resultsmentioning
confidence: 99%
“…Our chosen dynamical model has a truncated initial disk at 30 au, and our analyzed sample of Col-OSSOS colors was unable to rule out this scenario. Recent works have explored dynamical models with a low-mass disk extension beyond 30 au (e.g., Nesvorný et al 2020;Ali-Dib et al 2021). In the case of the inner neutral/outer red disk, the most probable color transition may have been pushed out further than 28 au if we had used a dynamical model with an extended disk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The dynamically cold KBOs at r = 42-45 au are predominantly VR which indicates r * < 42 au. If r * < 30 au, however, the dynamically hot populations such as Plutinos, hot classicals (HCs) and scattered disk objects (SDOs) would presumably have a much larger proportion of VR objects (Nesvorný et al 2020, Ali-Dib et al 2021. This indicates 30 < r * < 42 au.…”
Section: Introductionmentioning
confidence: 99%